Characteristics of cerebral venous thrombosis in patients from two university hospitals in Colombia between 2018-2020 - Ruiz, Adriana Marcela; Acelas , Gabriel Esteban; Patiño Rodriguez, Hernán Mauricio; Vergara, Jean Paul; Silva Soler, Miguel Arturo; Camargo, Maria Daniela (Biomedica, 2023)
Introduction. Cerebral venous thrombosis is an uncommon cause of cerebrovascular disease, which has been increasing worldwide. In Colombia, there are not enough recent studies that allow us to determine epidemiological characteristics of the disease in our population to identify more frequent risk factors and complications according to our living conditions. Objective. To describe clinical, demographic, and radiographic characteristics, and risk factors in a cohort of patients with cerebral venous thrombosis attended at two hospitals in Colombia. Materials and methods. Retrospective descriptive study with patients treated in the hospitalization neurology service of two hospitals in Bogotá, Colombia from December 2018 to December 2020. Results. Thirty-three patients were included. There was a higher incidence of cerebral venous thrombosis in women of childbearing age in the puerperium (n=7; 33.3%) and associated with autoimmune diseases (n=10; 30.3%). The most common initial symptom was headache (n=31; 93.9 %), followed by neurological focal signs (n=9; 27.2%) and seizures (n=8; 24.2%). Fifty-one percent (n=17) of the patients had a normal physical examination. Cerebral venous infarction occurred in 21.1 % (n=7), subarachnoid hemorrhage in 12.1 % (n=4), and intraparenchymal hematoma in 9 % (n=3) of all the patients. Sixty-point six percent (n=20) of the patients had a total independent Barthel functional scale. None of those died. Conclusions. We found similar sociodemographic, clinical, and radiography characteristics to those reported in the world literature. Regarding the differences, deep cerebral venous circulation was higher than that described in previous studies but without complications increase or mortality.